Thesis Supervision And Glitches Of Researchers - Nasreen Akhter, Fariha Sohil, Sabiha Iqbal, Kiran Mushtaq, Tahira Taj, Tamoor Shoukat (Migration Letters, 2024)
Research is an integral component for postgraduate studies. Students working on thesis/dissertation writing need skill to write research reports following approved SOPs of the institution of their studentship. This study was conducted to search out required skills that needs to be learnt before starting to write a thesis/dissertation for research degrees. Moreover, searching of weaker areas in research supervision was also a aim of this study. Qualitative model of research was adopted in this study. A sample of 47 research scholars having or working on thesis writing at last stage were selected for data collection. In light of data analysis, based on literature review and field data its was concluded that a research scholar needs; a skillful research supervisor, effective research training, art to trace and frame a valuable topic for research, literature search and its reporting skill adopting scholarly writing styles, resources detection and their utilization skill, a strong grip on research methodology and time management skill to write a valuable thesis. Moreover, in light of data from the field it was concluded that researchers face lot of issues regarding attitude of research supervisors. They reported that many supervisors do not try to be helpful for researchers. They don’t give proper time to their supervisees and try to solve their issues as a guide. Moreover, researchers reported financial issues in conduct of research and admitted that they were not successful to detect or utilize available financial assistance. Researchers also reported non cooperative behavior of their colleagues to tackle their issues.